Impact of Damper Windings on Unbalanced Steady-State Performance of Synchronous Generator connected to the 500 KV EHV Jamali System - Sugiarto Kadiman (Retii, 2018)
Unbalanced loads, such as unequal voltage magnitudes at the fundamental of both system frequency and phase angle deviation, are inrehent in 500 kV EHV Java-Madura-Bali (or Jamali) System. This crucial unbalanced loads may cause overheating of the machineries including synchronous generators (SG) which is a source of electrical energy generation system. To decrease the unbalance, damper windings are installed in SG. This study is to investigate the performance of three different damper winding configurations of a SG under unbalanced steady-state condition. By the SGs simulator, induced currents of damper windings under the unbalanced steady-state system conditions are measured and analyzed.  The value of the generator’s inputs is derived through unbalanced Newton-Raphson loadflow analysis on the Jamali System. Clearly that the damper windings have contributed the stability effectively and increased the maximum output. Moreover, there were little lower power angle of the SGs because the damper windings reduced the unbalanced loads.Keywords: damper windings, 500 kV EHV Jamali System, unbalanced steady state